Ultrasonography diagnosis of dumbbell−shaped C5 cervical schwannoma: a case report and literature review - Yu, Kailin; Chen, Jingsen; Pan, Minqiang; Xu, Kanlun; Huang, Pintong; Peng, Yucong (Frontiers in Oncology, 2025)
Introduction and importanceDumbbell-shaped C5 schwannomas are rare lesions that involve both intraspinal and extra-spinal communicating compartments. Early diagnosis and complete resection are of great significance in the treatment of dumbbell-shaped cervical schwannomas.Case presentationThe authors present a case of a 69-year-old female patient who has detected a palpable cervical mass for the preceding year. The patient had not sought medical consultation until pain and numbness in her right upper limb occurred over the span of two weeks. The initial ultrasound examination revealed a C5 dumbbell-shaped schwannoma with size of 6.07 cm * 2.54 cm, which expediting a timely magnetic resonance imaging (MRI) examination and subsequent surgical intervention for the patient.Clinical discussionDespite the majority being benign, spinal schwannomas are characterized by an insidious onset, with patients typically presenting for medical attention at a stage when they exhibit severe symptoms, including but not limited to cervical and shoulder pain, paresthesia of the limbs, and motor weakness. A definitive diagnosis is often confirmed through computed tomography (CT) or MRI. Regrettably, an extended disease duration can occasionally result in a degree of neurological dysfunction that is refractory to complete recovery. Notably, ultrasonography, as an accessible imaging modality, is equally capable of visualizing critical structures within and surrounding the spinal canal, facilitating the early detection and diagnosis of occult spinal schwannomas, particularly for dumbbell-shaped schwannomas involved intraspinal and extra-spinal compartments.ConclusionThis study highlights the relevance of ultrasonography for the initial evaluation, interdisciplinary and coordinated work in the management of spinal tumor.